(untitled) (Scientific journal of the Fergana State University, 2024)
The article analyzes the reflection in archival documents of information on the state of the education system in Turkestan, in particular in the Fergana region, issues of illiteracy, and the creation of new Soviet schools after the October coup in Russia. The national and gender composition of school students, as well as their age differences, are also covered. In addition, issues of forming a supply system and its distribution in technical schools, schools and kindergartens were also discussed. The article also analyzes valuable information about the organization of the admission process to educational institutions that ensure the production of personnel for the national economy, reflected in the funds of the state archive of the Fergana region.